Ceftazidime-avibactam susceptibility among KPC-producing enterobacterales in southern Brazil - Kehl Moreira, Natália (2023)
Carbapenem-resistant Enterobacterales (CRE) are a subject of global concern as limited therapeutic options are available. New combinations of β-lactams and β-lactamase inhibitors, such as ceftazidime-avibactam (CAZ-AVI), have recently been approved in Brazil for the treatment of CRE infections. Cases of resistance during treatment or even without previous CAZ-AVI use have been published and it is worrisome in scenarios where KPC-producing Gram-negative bacilli are endemic, as in Brazil. We aimed to assess CAZ-AVI susceptibility among a CRE population recovered from hospitalized patients in Southern Brazil from 2015 to 2021. CAZ-AVI minimal inhibitory concentration (MIC) was determined by antibiotic gradient strips. All the 238 evaluated KPC-producing Enterobacterales were susceptible to CAZ-AVI (MIC = 0.25 to 8 µg/mL), with seven isolates presenting borderline MICs (8 µg/mL). Considering the clinical importance of this new antibiotic in Brazil, we emphasize the importance of surveillance studies to eventually detect resistance phenotypes or even increasing CAZ-AVI MICs.